Correction: Shah et al. VIV-Based Energy Harvesting from Tandem Cylinders for Self-Sustained IoT Systems. Eng. Proc. 2024, 75, 40 - Muhammad Mahad Shah; Arslan Ahmed; Usman Latif; Syed Maaz Hasan; Emad Uddin (Engineering Proceedings)
Additional Affiliation [...]